2012
DOI: 10.4103/2230-8210.100676
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and cut-off point of vitamin D deficiency among secondary students of Arak, Iran in 2010

Abstract: Introduction:Vitamin D has a basic role in bone growth and metabolism and has been noticed for its important role in many diseases, such as diabetes, depression, hypertension, and cardiovascular disease. Regarding some studies, detection of vitamin D deficiency in different places has important implication for health. This study determined prevalence of vitamin D deficiency in Arak, a centrally located city in Iran.Materials and Methods:Based upon a cross-sectional study in 2010, 420 students 10--16 years old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…with reports of deficiency in >80% of the adolescence in Tehran and Arak [17,18], about 60% of school-age girls in Yazd [19] and >70% in newborn infants in Zanjan [20]. Few foods naturally contain enough vitamin D , the most natural way to get vitamin D is cutaneous production when skin is exposed to the sunlight [3].…”
Section: Introductionmentioning
confidence: 99%
“…with reports of deficiency in >80% of the adolescence in Tehran and Arak [17,18], about 60% of school-age girls in Yazd [19] and >70% in newborn infants in Zanjan [20]. Few foods naturally contain enough vitamin D , the most natural way to get vitamin D is cutaneous production when skin is exposed to the sunlight [3].…”
Section: Introductionmentioning
confidence: 99%
“…Some novel investigations have shown that the chance of non-melanoma skin cancers in people with high vitamin D levels is lower as much as 47% (2). There was no significant difference in the serum level of vitamin D between the patient and control groups, which is not consistent with other studies in this area (2,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). This may be due to an increase in the ratio of vitamin D deficiency in the general population, which caused no significant differences.…”
Section: Discussionmentioning
confidence: 59%
“…Such a delay, made many others to do the same researches. Even well after 2008 many papers were published concerning the same issue and all emphasized on the importance of the consequences (23,(28)(29)(30)(32)(33)(34) (50) and bread (51).…”
Section: Discussionmentioning
confidence: 99%